2013 International Conference on Machine Intelligence and Research Advancement 2013
DOI: 10.1109/icmira.2013.37
|View full text |Cite
|
Sign up to set email alerts
|

Modified Optimum Beamforming for Smart Antenna in WCDMA Network

Abstract: Third-Generation based Wide Band Code DivisionMultiple Access (W-CDMA) networks have been characterized for high data rate services accessible to a large number of users. But multipath and co-channel interference puts a limit on system capacity, throughput and new multimedia information services like wireless internet or video streaming. Smart antenna technique that includes Direction of Arrival (DOA) approach and Adaptive Beamforming algorithm is a promising means to improve the over-all system capacity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Simulation results revealed that MUSIC is the more effective option to use for high velocity sources and poor channel conditions, same results as reported by Vesa [79], Sawada et al [80], and Singla and Saxena [81].…”
Section: Beamforming-based Schemessupporting
confidence: 84%
“…Simulation results revealed that MUSIC is the more effective option to use for high velocity sources and poor channel conditions, same results as reported by Vesa [79], Sawada et al [80], and Singla and Saxena [81].…”
Section: Beamforming-based Schemessupporting
confidence: 84%
“…Singla [14] proposed a data-dependent criteria to improve the MVDR weight. This method used constraints function instead of a single linear equality constraint.…”
Section: Related Workmentioning
confidence: 99%
“…In general, any uplink signal from the MS can be used to estimate the AoA, but typically a known signal such as the Sounding Reference Signals (SRSs) or DeModulation Reference Signals (DM-RS) would be used [12]. In order to construct the shape of the downlink beam, direction of arrival estimation already exists and is supported in WCDMA but it is not standardized [13]. According to the angle of arrival, the cell is divided into ranges like in figure 2 relative to the angle between the UE, the BS and the geographical north.…”
Section: A Network Used Metricsmentioning
confidence: 99%